Assessment of the Transmission Dynamics of Clostridioides difficile in a Farm Environment Reveals the Presence of a New Toxigenic Strain Connected to Swine Production - Alves, Frederico; Nunes, Alexandra; Castro, Rita; Sequeira, António; Moreira, Olga; Matias, Rui; Rodrigues, João Carlos; Silveira, Leonor; Gomes, João Paulo; Oleastro, Mónica (Frontiers in Microbiology, 2022)
The recent increase in community-acquired Clostridioides difficile infections discloses the shift in this bacterium epidemiology. This study aimed at establishing a transmission network involving One Health components, as well as assessing the zoonotic potential and genomic features of dominant clones. Samples were collected from different compartments of animal, human and environmental origin, from an animal production unit. C. difficile isolates were characterized for toxigenic profile by multiplex-PCR, while genetic diversity was evaluated by PCR-ribotyping and whole genome-based analysis. The overall C. difficile prevalence was 37.2% (70/188), and included samples from environmental (58.3%, 35/60) and animal (31.5%, 35/111) compartments; human samples (n=17) taken from healthy workers were negative. A predominant clone from RT033 was found in almost 90% of the positive samples, including samples from all compartments connected to the pig production unit, with core-genome single nucleotide variant (SNV)-based analysis supporting a clonal transmission between them (mean distance of 0.1±0.1 core-SNVs). The isolates from this clone (herein designated PT RT033) were positive for all C. difficile toxin genes (tcdA, tcdB, cdtA/cdtB). The phylogenetic positioning of this clone was clearly distinct from the classical RT033 cluster, suggesting a different evolutionary route. This new clone shares genomic features with several RTs from the clade 5 Sequence Type (ST) 11, including a complete pathogenicity locus (PaLoc) that is more similar to the one found in toxigenic strains and contrasting to the less virulent classical RT033 (tcdA-, tcdB-, cdtA+/cdtB+). The presence of a tcdA gene truncated into two ORFs, not previously described, requires further evaluation concerning toxin functionality. We hypothesize that the unique combination of genetic elements found in the PT RT033 clone may contribute to host tropism and environmental dissemination and maintenance. This study constitutes the first report of a toxigenic RT033 clone and adds to the overall knowledge on Clade 5 sequence type 11, considered the C. difficile evolutionary lineage with the highest zoonotic potential. The presence of this clone in all compartments associated with the pig production unit suggests a transmission chain involving these animals and contributes to unveil the role played by animal and environmental reservoirs in this pathogen epidemiology.